Bell’s Palsy After Second Dose of Moderna COVID-19 Vaccine: Coincidence or Causation? - Pothiawala, Sohil (Acta medica Lituanica, 2021)
US Food and Drug Administration (FDA) recommended enhanced safety surveillance to monitor for cases of Bell’s palsy following Moderna vaccine administration in larger populations. The author reports a patient who developed right sided Bell’s palsy 2 weeks after administration of the second dose of Moderna COVID-19 vaccine. Considering this development of symptoms 2 weeks after the second dose of Moderna vaccine administration, there remains a possibility of a causal association. As more people get vaccinated, more information may be available in the future to establish association. Physicians need to maintain enhanced safety surveillance to monitor for cases of Bell’s palsy following mRNA vaccine administration.